2020
DOI: 10.1016/j.physio.2019.08.013
|View full text |Cite
|
Sign up to set email alerts
|

Validity of the International Physical Activity Questionnaire Short Form (IPAQ-SF) as a measure of physical activity (PA) in young people with cerebral palsy: A cross-sectional study

Abstract: Objectives The aim of this study was to examine the validity of the International Physical Activity Questionnaire Short Form (IPAQ-SF) as a measure of physical activity (PA) in young people with cerebral palsy (CP). Design Cross-sectional. Setting Participants were recruited through 8 National Health Service (NHS) trusts, one school, one university and through organisations that provide services for people with disabilities in England. Participants Sixty-four, ambulatory young people aged 10-19 years with CP [… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 27 publications
0
42
0
Order By: Relevance
“…Specifically, for children with CP, the feasibility of existing questionnaires is limited owing to their length and the time required for the parents to complete them, as well as for the clinician to evaluate them. 16 Moreover, existing instruments have not included sedentary behaviour (as part of physical activity) nor considered sleep to be part of the (24-hour) physical activity spectrum. Using questions from previously validated questionnaires developed for other paediatric populations, such as the Family Nutrition and Physical Activity screening tool, 17 and physical activity recommendations for children with CP, 1 we have applied a structured approach with interviews involving both health professionals and parents of children with CP to adapt items and construct the new checklist.…”
Section: Item Generation and Content Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, for children with CP, the feasibility of existing questionnaires is limited owing to their length and the time required for the parents to complete them, as well as for the clinician to evaluate them. 16 Moreover, existing instruments have not included sedentary behaviour (as part of physical activity) nor considered sleep to be part of the (24-hour) physical activity spectrum. Using questions from previously validated questionnaires developed for other paediatric populations, such as the Family Nutrition and Physical Activity screening tool, 17 and physical activity recommendations for children with CP, 1 we have applied a structured approach with interviews involving both health professionals and parents of children with CP to adapt items and construct the new checklist.…”
Section: Item Generation and Content Reviewmentioning
confidence: 99%
“…Unfortunately, the current physical activity measurement tools are not practical for implementation in routine care. Specifically, for children with CP, the feasibility of existing questionnaires is limited owing to their length and the time required for the parents to complete them, as well as for the clinician to evaluate them 16 . Moreover, existing instruments have not included sedentary behaviour (as part of physical activity) nor considered sleep to be part of the (24‐hour) physical activity spectrum.…”
Section: Development Of the 24‐hour Activity Checklistmentioning
confidence: 99%
“…2.3.1 The International Physical Activity Questionnaire-Short Form (IPAQ-SF) There are various questionnaires to determine the physical activity levels (Lee et al, 2011). It was indicated that IPAQ-SF version is one of the most appropriate and widely used self-report form to assess physical activity levels (Tierney et al, 2015;Lavelle et al, 2019). IPAQ is designed to evaluate the young people/middle-aged adults and special groups' physical activity levels (Craig et al, 2003).…”
Section: Data Collection Toolsmentioning
confidence: 99%
“…It consists of seven questions to measure average daily time spent walking, sitting and participating in activity of moderate and high intensity and produces a physical activity score based on last seven days (Tierney et al, 2015;Sanda et al, 2017;Lavelle et al, 2019).…”
Section: Data Collection Toolsmentioning
confidence: 99%
“…While there are several valid and reliable tests for motor capacity that are part of routine clinical assessments, measures of motor performance are mainly questionnaire-based [ 15 ], which makes them subject to biases [ 16 ]. However, in recent years, inertial measurement units (IMUs) have emerged to accurately measure walking performance and PA parameters in children with CP [ 17 , 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%